Sexual activities before and after the Carnaval and the risc of acquiring DST/ HIV/Aids, in Rio Branco, Acre -Brazil - Lopes, Creso Machado; Rigau, Jose Manuel Moraes (Brazilian Journal of Sexually Transmitted Diseases, 1999)
Transversal analytical poll, covering 752 fo-liões (carnival players) in Rio Branco - Acre -Brazil in the year 1997. The subjects were 409 (54.4%) fe-males and 343 (45.5%) males. The oldest subjects ranged from 20 1-129 year of age and comprised 44.4% ofinformants. Of all subjects, 70.0% were sin-gle. And the topics investigated were aspects of the sexual behavior and the risk of catchin g DST / HIH and Aids before and during the carnival period. The-re was no significant increase of the number of se-xual relations but tbere was na increase in the chan-ge of partners. The habit of carryng condoms was stronger during the carnival. it was verified virtue of the use condoms. The campaigns of prevenction were evaluated as excellent and good by 87.7% of the informants.